ANALISIS PERILAKU HERDING PADA SAHAM SEKTOR BANK DIGITAL YANG TERDAFTAR DI BEI PERIODE 2021 - Priscillia, Anita; Vietha Devia SS (Contemporary Studies in Economic, Finance and Banking, 2023)
This research was conducted to detect and identify herding behavior that might occur in digital bank sector stocks in the 2021 period. The 2021 period is used for the market when market conditions are stressful and high returns. The approach method of Chang et al. (2000), namely CSAD-Cross Sectional Absolute Deviation to calculate return dispersion values ​​and use quantile regression analysis to detect herding behavior. The data used is secondary data, in the form of monthly stock return data and market returns for digital bank stocks. The results of this study indicate that digital bank stocks in 2021 have no indication of herding behavior. This means that Indonesian investors acted rationally during the COVID-19 pandemic.